Databook of antioxidants - Wypych, Anna; Wypych, George (ChemTec Publishing, 2020)
"The databook contains information on antioxidants both natural and man-made. Their significant applications include components of natural products (e.g., fruits, vegetable, herbs, nuts, chocolate, etc.), used as food preservatives and supplements, fuels, lubricants, polymers, rubbers, and their derivative products. Regardless of the application materials of similar composition are applied for the purpose, and similar mechanisms are involved in their performance. The information on each antioxidant included in the Databook of Antioxidants is divided into five sections: General information, Physical properties, Health and safety, Ecological properties, and Use & Performance. The data belong to over 100 data fields, which accommodate a variety of data available in source publications."--